Gray hat hacking the ethical hacker's handbook - Harper, Allen; Regalado, Daniel; Linn, Ryan; Sims, Stephen; Spasojevic, Branko; Martinez, Linda; Baucom, Michael; Eagle, Chris; Harris, Shon (McGraw-Hill Education, 2018)
Fortify your network and avert digital catastrophe with proven strategies from a team of security experts. Completely updated and featuring 13 new chapters, "Gray Hat Hacking: The Ethical Hacker's Handbook, Fifth Edition" explains the enemy's current weapons, skills, and tactics and offers field-tested remedies, case studies, and ready-to-try testing labs. Find out how hackers gain access, overtake network devices, script and inject malicious code, and plunder web applications and browsers. Android-based exploits, reverse engineering techniques, and cyber law are thoroughly covered in this state-of-the-art resource. The new topic of exploiting the Internet of things is introduced in this edition. -- From publisher's description
Revised edition of: Gray hat hacking : the ethical hacker's handbook / Allen Harper [and others]. - Includes bibliographical references and index. - Print version record
Keywords: Penetration testing (Computer security) -- Handbooks, manuals, etc; Computer security -- Handbooks, manuals, etc; Hackers; Tests d'intrusion; Guides, manuels, etc; Sécurité informatique; Guides, manuels, etc; Pirates informatiques; Computer security; Penetration testing (Computer security); handbooks; Handbooks and manuals; Guides et manuels; Handbook